Traditional Knowledge About Polar Bears (Ursus maritimus) in East Greenland: Changes in the Catch and Climate Over Two Decades - Laidre, Kristin L.; Northey, Allison D.; Ugarte, Fernando (Frontiers in Marine Science, 2018)
In Greenland, polar bears (Ursus maritimus) are nutritional, economic, and cultural subsistence resources for Inuit. Traditional Ecological Knowledge (TEK) collected from subsistence hunters can provide important insights and improve management decisions when collected systematically. We report on the results of a TEK survey of subsistence polar bear hunters living in the areas around Tasiilaq and Ittoqqortoormiit, East Greenland. Twenty-five full-time polar bear hunters were interviewed between December 2014 and March 2015 in a conversation-style interview, where a local interviewer fluent in the East Greenlandic dialect asked a series of 55 predetermined questions. The primary goals were to 1) gather Inuit perspectives on polar bear subsistence quotas and hunting strategies, 2) understand how climate change is affecting the polar bear subsistence hunt, and 3) document observed changes in polar bear distribution, abundance, and biology. Approximately 40% of the Tasiilaq respondents had caught between 10-19 polar bears in their lifetime, while 67% of Ittoqqortoormiit respondents reported lifetime catches of >20 bears. In both areas, polar bears were most commonly hunted between February and April. Hunters noted large changes to the climate in the areas where they hunt polar bears. Most hunters reported loss of sea ice, receding glaciers, unstable weather, and warmer temperatures. In Tasiilaq 73% of the hunters said climate changes had affected the polar bear hunt and in Ittoqqortoormiit about 88% of respondents reported the same. Hunters indicated that sea ice loss has created more areas of open water so dog sledges have become unsafe for hunting transportation compared to 10-15 years ago (reported by 100% of hunters in Tasiilaq and 80% in Ittoqqortoormiit). In both areas hunters noted that more polar bears are coming into their communities compared to 10-15 years ago (81% of Tasiilaq hunters and 78% of Ittoqqortoormiit hunters) and pointed to the introduction of quotas and loss of sea ice as potential reasons. This study provides an important perspective on the East Greenland subpopulation of polar bears that can be used to direct science questions and inform management.